Efficacy and safety of PD-1/PD-L1 inhibitors in the treatment of recurrent and refractory ovarian cancer: A systematic review and a meta-analysis - Zeng, Siyuan; Liu, Daju; Yu, Yongai; Zou, Lei; Jin, Xianyu; Liu, Bing; Liu, Lifeng (Frontiers in Pharmacology, 2023)
Abstract Objective: To explore the efficacy and safety of PD-1/PD-L1 inhibitors in treating recurrent/refractory ovarian cancer (OC). Methods: The online databases, including PubMed, Embase and Cochrane Library, were searched for relevant literatures on exploring the efficacy and safety of PD-1/PD-L1 inhibitors in the treatment of recurrent/refractory OC. The keywords are as follows: ovarian neoplasms, programmed death receptor, PD-1, PD-L1, immunotherapy, and immune checkpoint inhibitor. Furthermore, qualified studies were screened for further meta-analysis. Results: In this study, 11 studies (990 patients) were analyzed to evaluate the efficacy of PD-1/PD-L1 inhibitors in the treatment of recurrent/refractory OC. The combined results proved that the objective response rate (ORR) was 6.7%, 95% CI (4.6%,9.2%), disease control rate (DCR) was 37.9%, 95% CI (33.0%, 42.8%), median overall surviva (OS) was 10.70 months, 95% CI (9.23, 12.17), and median progression free survival (PFS) was 2.24 months, 95% CI (2.05, 2.43). In addition, in terms of the safety of patients suffering from recurrent/refractory OC and receiving PD-1/PD-L1 inhibitors, the combined treatment related adverse events (TRAEs) were 70.9% (61.7% - 80.2%), and the combined immune related adverse events (iAEs) were 29%, 95% CI (14.7%, 43.3%). Conclusions: In patients with recurrent/refractory OC, PD-1/PD-L1 inhibitors were used alone and there was no obvious evidence of improved efficacy and survival. As for safety, the incidences of TRAEs and iAEs are high, so PD1/PD-L1 inhibitors should be applied according to individual conditions.Trial Registration: CRD42022367525